The book of two ways : [large type] a novel - Picoult, Jodi, 1966- (Thorndike Press large print basic, 2020)
"Dawn Edelstein's life instantly changes when the plane she's on crashes. Before impact, she thinks not of her husband but of a man she last saw fifteen years ago: Wyatt Armstrong. Dawn, miraculously, survives the crash. She could return [to] Boston, back to her husband, their beloved daughter, and her work as a death doula. Or she could go to Egypt to find Wyatt, who works as an archaeologist, a career Dawn once studied for but abandoned. She could potentially complete her research on The Book of Two Ways--the first known map of the afterlife. As the story unfolds, Dawn's two possible futures unspool side by side, as do the secrets and doubts long buried with them"--Page 4 of cover.